A Systematic Review of Research on Late Spring Frost and its Estimation Methods - Mobina Abdollahi Fuzi; Bahram Bakhtiari; Kourosh Qaderi (Nīvār)
The late spring frost damage has been one of the significant natural hazards. Spring frost is considered an important threat to agricultural products. The aim of this study is to find the answers to these questions. "How does a late spring frost affect agricultural crops?" and "What are the gaps in recent research?" Several articles were collected from Web of Science, Scopus, Science Direct, Pub Med, ResearchGate and Google Scholar search engine, SID, Iran Doc, Magiran, and Si explore the databases until November 2022. In order to find relevant publications, “Spring Frost”, “Late Frost” and “Late Spring Frost” were used as the keywords. After evaluating the articles, 45 articles were selected. Recent studies have shown that 42.22% of the articles were related to damage inflicted by late spring frost. 53.33% of that were published in Asia. Most articles were published in Iran and other parts of the world in 2014 and 2018, respectively. The words "Frost Damage", "Phenology", "Climate Change" and "Frost Spring" appeared as the most frequent keywords. In addition, the results showed that the damage caused by the LSFs (Late Spring Frosts) significantly affects vulnerable plant organs markedly affects. Late-spring frosts occurring after the germination of herbaceous plants and trees have an important impact on agriculture and forestry in regions of the world. This event has caused more economic losses to agriculture than any other climatic hazard in Asia, North America, and Europe. However, the severity of damage due to LSF may be amplified by climate change.